Portuguese Polar Program: Annual Report 2019 - Cabrita, Maria Teresa (2020)
This Annual Report of the Portuguese Polar Program, PROPOLAR reports the main activities conducted between August 2018 and December 2019 The PROPOLAR is led by the CEG/IGOT University of Lisbon, under a Coordinating Committee that includes members of other 4 Portuguese research institutions CCMAR University of the Algarve, MARE University of Coimbra, CQE University of Lisbon, and CIIMAR University of Oporto The Program is funded by the Fundação para a Ciência e a Tecnologia MCTES FCT) as a development of its former Polar Office The activities herein disclosed reflect a very busy and inspiring year The PROPOLAR supported fifteen projects that were successfully carried out in the Arctic and Antarctica Logistics continued to be based on international cooperation and on a Portuguese funded Antarctic flight open to partner programs Logistical support in Antarctica was mainly provided by Spain, Chile and the Republic of Korea, also with strong cooperation in research and facilities with Argentina, Brazil, Bulgaria, China, Peru, Turkey, United States of America and Uruguay Participation in international meetings and workshops, as well as the organisation of a symposium and an international meeting, and the support provided to the Portuguese Conference on Polar Science, fulfilled and enriched this very active period, also helping to reinforce the credibility and relevance of the program in the international polar arena B ringing together all these efforts and resources will surely attract and mobilise more young researchers into a Polar scientific career, thus ensuring the future of the Portuguese Polar science, and that the program will continue to blossom We are confident that the successes that PROPOLAR has had in 2019 will serve as an impetus for our very dynamic and committed community of polar researchers to move forward in in vesting in the future of the Portuguese P olar science and preparing to seize new opportunities